Topological protection of multiparticle dissipative transport - Johannes Loehr (Nature Portfolio, 2016)
Transport of a collection of classical particles involves thermal ratchet effect or adiabatic motion, which brings complexity to control multiparticle transport. Here, Loehr et al. show topologically protected multiparticle transport of diamagnetic and paramagnetic colloids, driven by periodic modulation loops of an external magnetic field.